Mutational spectrum and profile of breast and ovarian cancer patients in Saudi Arabia’s western region: single center experience - Ekram, Samar N.; Elemam, Omima; Alandonisi, Munzir; Flemban, Arwa; Samkari, Jamil; Zainuddin, Hassan H.; Azher, Zohor; Tashkandi, Emad; Mufti, Ahmad; Khogeer, Asim (Discover. Oncology, 2025)
Background The incidence of breast cancer (BC) and ovarian cancer (OC) has increased in Saudi Arabia. The western region of Saudi Arabia presents a unique population with distinct genetic backgrounds, making it vital to investigate the prevalence of BC/OC-associated gene mutations in this area. This study aimed to determine the prevalence and mutational profiles of BC and/or OC predisposing genes in the western region of Saudi Arabia, and to characterize the associated phenotypes in individuals carrying these mutations. Methods We employed next-generation sequencing (NGS) to identify the mutational spectra of 209 Saudi Arabian patients with BC and/or OC from the Western region. Results 51/209 (24.4%) patients had a mutation in one of the BC/OC predisposing genes. Overall, 34, 10, and 7 PV/LPV were identified in BRCA1 , BRCA2 , and other genes, respectively. Mutations in BRCA1 were predominant and strongly related to high-grade, triple-negative BC. BRCA1 NM_007294.4:c.1140dup p.(Lys381Glufs*3), NM_007294.4:c.5095C > T p.(Arg1699Trp), NM_007294.4:c.4986 + 6 T > C (p.?), NM_007294.4:c.5251C > T p.(Arg1751*), and NM_007294.4:c.5067_5074 + 1del p.(Met1689Ilefs*3) were recurrent with NM_007294.4:c.3217_3218del p.(Gly1073*), NM_007294.4:c.5067_5074 + 1del p.(Met1689Ilefs*3), and NM_007294.4:c.5234del p.(Asn1745Thrfs*20) being novel. The combined frequency of recurrent mutations in BRCA1 was 42%. Concerning BRCA2 , we identified a recurrent variant NM_000059.4:c.7480C > T p.(Arg2494*) and two novel variants NM_000059.4:c.643del p.(Glu215Lysfs*15) and NM_000059.4: EXon1-8del. Conclusion In our study, we identified a high prevalence of BRCA1 /2 variants in the western region of Saudi Arabia, offering novel and important insights specific to this area. We also identified other gene variants, though their impact remains unclear due to the limited sample size. This work represents an important first step in understanding the genetic factors contributing to breast and ovarian cancer in the Western region. It underscores the urgent need for larger studies to comprehensively explore the genetic landscape and better understand how these variants influence cancer risk in this population.